2012
DOI: 10.1016/j.jvs.2011.10.125
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Lab 360: Are we losing control?

Abstract: The editors and reviewers of this article have no relevant financial relationships to disclose per the JVS policy that requires reviewers to decline review of any manuscript for which they may have a competition of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“… 42–44 As a result, vascular surgeons are losing the battle to exclusively perform endovascular procedures at the community level. 45 This serves as a stark warning that although healthcare practitioners from different families possess varying skills, when performing the same procedure, evolutionary principles are forefront; not who believes he or she can execute the procedure better.…”
Section: Nutritionally Rich Renumeration: Aesthetic/cosmetic Surgerymentioning
confidence: 99%
“… 42–44 As a result, vascular surgeons are losing the battle to exclusively perform endovascular procedures at the community level. 45 This serves as a stark warning that although healthcare practitioners from different families possess varying skills, when performing the same procedure, evolutionary principles are forefront; not who believes he or she can execute the procedure better.…”
Section: Nutritionally Rich Renumeration: Aesthetic/cosmetic Surgerymentioning
confidence: 99%
“…The consensus among vascular surgery educators is that it is important to provide vascular surgery residents and fellows with formal NIVL training to prepare them to not only pass the RPVI exam but also acquire expertise in reading studies as practitioners and ability to supervise sonographers. 2,6,7 The 2011 Eastern Vascular Society Vascular Laboratory Survey showed that many practicing vascular surgeons are frustrated that vascular studies are being done at NIVL directed by nonvascular specialists, who they claim are unable to correctly interpret vascular testing. This has apparently resulted in the need for repeat vascular laboratory testing at NIVL managed by vascular surgeons, which may not always be reimbursed by insurance companies.…”
Section: Introductionmentioning
confidence: 99%
“…This has apparently resulted in the need for repeat vascular laboratory testing at NIVL managed by vascular surgeons, which may not always be reimbursed by insurance companies. 7 In 2015, ARDMS also reported a survey of 2,473 registrants credentialed since 2010 with a participation rate of 38.2% of whom 92.8% (944) physicians were in active practice. 8 In the survey, 42% were cardiologists, 36% were vascular surgeons and the rest were radiologists, vascular medicine specialists, and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation